Transformasi Peran Guru Sebagai Fasilitator Deep Learning di Kelas - Waluyo Waluyo; Maria Ulfa; Fitrotun Nahdiyah; Afif Luthfi (JOURNAL SAINS STUDENT RESEARCH, 2025)
The advancement of 21st-century education demands a paradigm shift in teaching practices, including the transformation of teachers' roles from content deliverers to active facilitators. This study aims to describe the transformation of teachers' roles as facilitators in deep learning-based classroom instruction, particularly at MTs N 1 Rembang di Provinsi Jawa Tengahin Central Java Province. Addressing the persistent dominance of conventional teaching methods, this research explores how teachers transition into active facilitators who encourage student exploration, reflection, and independent learning. A descriptive qualitative approach was employed, with data collected through interviews, observations, and document analysis. The findings reveal that teachers have begun to implement contextual, interactive, and project-based learning while utilizing educational technology and formative assessment strategies. Three primary facilitator roles of teachers in deep learning contexts were identified: as motivators of learning, connectors to relevant learning resources, and assessors of students’ learning processes. This transformation encourages students to become active agents in constructing meaningful and life-relevant knowledge. Institutional support and ongoing professional development are essential to help teachers fully optimize their facilitative roles.